(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
Difficulty in travelling has always been a problem for visually impaired people in their daily lives, and smart wearable devices have shown great potential in helping the visually impaired to travel by their portability and interactivity. Therefore, this paper provides an overview of smart wearable devices that assist the visually impaired in travelling. The paper first analyses the characteristics of visually impaired people to understand their needs, and then briefly reviews the history of travel assistance devices. The paper then analyses the working mechanisms of smart wearable devices and divides them into three categories based on how they return information to the user. Then, the paper summarises the advantages and disadvantages of different types of devices and the disadvantages common to all types by detailing the working principles, functions, and usage effects of a dozen different types of devices. Finally, it summarises the current research status and limitations, and proposes future research directions. It aims to provide a reference for the development of smart wearable devices that assist visually impaired people in travelling.